Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages BEVERIDGE GOVERNMENT PENSIONS 4 Old-age pensions to rise (after 20 years) to 24s. single and 40s. for a couple. Immediate increase of 40 per cent, for a couple, and 25 per cent, for a single person. 4 Rise of old age pensions (after 20 years) to Beveridge levels categorically rejected. Proposed slightly higher immediate increase than that suggested by Beveridge. 5 Unconditional widows' pensions abolished. Widows' benefit 13 weeks at 36s. per week. Guardians' benefit (while there are dependent children) 24s. per week. 5 Nothing definite said with regard to widows' scales of benefit. Hint of mean test in Sir John Anderson's speech. Claim that Government would be kinder to elderly widows than Beveridge. COMPENSATION 6 Workmen's Compensation to be taken out of "atmosphere of litigation." Sick pay scales for 13 weeks and then two-thirds of wages. 6 Further consideration to be given. Proposal for higher benefit after 13 weeks "Difficult to justify." CHILDREN'S ALLOWANCES 7 A — Children's Allowances of 8s. per week for second child of employed person. B — 8s. for first child when person is in benefit. C — Assumption that existing child welfare services, valued at 1s. per head per week, will continue. Thus total allowance of 8s. in cash plus 1s. child welfare services = 9s. 7 A Children's allowances of 5s. per week for second child of employed person. B — Further consideration of an allowance for first child of those on benefit. C — Promise to increase existing child welfare services to value of 2s. 6d. per head per week. Thus total allowance of 5s. cash, plus 2s. 6d. child welfare services = 7s. 6d. HEALTH SERVICE 8 Comprehensive medical service, covering all types of treatment and open to all citizens. 8 Accepted subject to retention of voluntary hospitals, and right of doctors to continue private practice. 25 15X/2/103/272